DEVELOPMENT OF REAL-TIME MULTI-LOCATION INVENTORY SYSTEM AT PT. AFA KARYALOKA NATA UTAMA USING V-MODEL - Sa’banna Hasibuan, Arif; Setiadi, Tedi; SA'BANNA HASIBUAN, ARIF (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2025)
Inventory management in companies with multiple locations often faces challenges when conventional tools such as spreadsheets are still used, causing inefficiency and difficulties in maintaining accurate records. Previous studies have largely focused on single-location systems without real-time integration, leaving a gap in supporting centralized and synchronized inventory control. This study aims to develop a web-based inventory information system that supports real-time and multi-location operations to improve efficiency and accuracy in stock management. The system was developed using the V-Model methodology, which includes requirements analysis, system design, architectural design, module design, implementation, and testing. Research data were obtained through interviews with company employees and literature review. System testing was conducted using the Black Box Testing method, which focuses on validating functionality based on inputs and outputs without producing quantitative data. Therefore, the evaluation was based on the conformity of the system with the specified requirements. The results show that the developed system is capable of handling core functions such as warehouse and counter stock management, shipping records, return records, and user management, all integrated into a centralized database with real-time synchronization across locations. This ensures that inventory data remains consistent and up to date. In conclusion, the research successfully addresses the identified gap by presenting a web-based, multi-location inventory information system with real-time integration, thereby supporting greater efficiency, accuracy, and control in inventory management.